2020
DOI: 10.48550/arxiv.2010.13988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward Better Generalization Bounds with Locally Elastic Stability

Zhun Deng,
Hangfeng He,
Weijie J. Su

Abstract: Classical approaches in learning theory are often seen to yield very loose generalization bounds for deep neural networks. Using the example of "stability and generalization" (Bousquet & Elisseeff, 2002), however, we demonstrate that generalization bounds can be significantly improved by taking into account refined characteristics of modern neural networks. Specifically, this paper proposes a new notion of algorithmic stability termed locally elastic stability in light of a certain phenomenon in the training o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…We show that the transformations used by ContRE would not significantly affect the generalization estimation, by additionally reporting the correlations between transformed training and testing data, i.e., L 𝜽 (𝑅(𝒁 )) and L 𝜽 (𝑅(𝒁 𝑑𝑒𝑠𝑑 )) (0.983, 0.903 and 0.989 for CIFAR10, CIFAR100 and ImageNet respectively), but for further extensions, transformations should be cautiously chosen. (2) Theoretical analyses of local elasticity [3,11,15] seems related to our approach, but theoretical links among contrastive examples, generalization performance and this notion are not available yet. (3) Lack of appropriate data transformations, it would be difficult to extend to other data formats, such as texts, audios, graphs etc.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We show that the transformations used by ContRE would not significantly affect the generalization estimation, by additionally reporting the correlations between transformed training and testing data, i.e., L 𝜽 (𝑅(𝒁 )) and L 𝜽 (𝑅(𝒁 𝑑𝑒𝑠𝑑 )) (0.983, 0.903 and 0.989 for CIFAR10, CIFAR100 and ImageNet respectively), but for further extensions, transformations should be cautiously chosen. (2) Theoretical analyses of local elasticity [3,11,15] seems related to our approach, but theoretical links among contrastive examples, generalization performance and this notion are not available yet. (3) Lack of appropriate data transformations, it would be difficult to extend to other data formats, such as texts, audios, graphs etc.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Corneanu et al [8] define DNNs on the topological space and estimate the gaps from the topology summaries. Note that ContRE could be loosely guaranteed through data-dependent theoretical bounds [3] and potentially related to the local elasticity [11,15] while the theoretical adaptation to DNN models should be more cautiously considered. We leave this as future work.…”
Section: Contrastive Learning and Contrastivementioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that stability is closely related to the fundamental problem of learnability (Rakhlin et al, 2005;Shalev-Shwartz et al, 2010). Hardt et al (2016) pioneered the generalization analysis of SGD via stability, which inspired several upcoming work to understand stochastic optimization algorithms based on different algorithmic stability measures, e.g., uniform stability (Chen et al, 2018;Lin et al, 2016;Madden et al, 2020;Mou et al, 2018;Richards et al, 2020), argument stability (Bassily et al, 2020;Lei & Ying, 2020;Liu et al, 2017), on-average stability (Kuzborskij & Lampert, 2018;Lei & Ying, 2021a), hypothesis stability (Charles & Papailiopoulos, 2018;Foster et al, 2019;London, 2017), Bayes stability (Li et al, 2020) and locally elastic stability (Deng et al, 2020).…”
Section: Related Workmentioning
confidence: 99%